Large Online Courses: A Constraint on Instructor Presence and Higher-Level Thinking - Carozza, Linda; Davis, Hilary (Teaching and Learning Inquiry, 2025)
A growing body of literature claims instructor presence is crucial in an online course learning environment. In this paper, the authors contribute to this literature with empirical research related to instructor presence and how class size influences it. This study investigated whether class size was predictive of students’ ratings of instructor presence. The findings of this study suggest that in courses with higher-level skills as learning objectives, as the class size increased, students rated instructor presence lower. This result affirms existing research that explains courses that encompass constructivist skills or higher-level thinking benefit from the community of inquiry model. This model makes clear that instructor presence is imperative for effective student learning, and the implication of this directive is that class size needs to be adjusted (in many cases, it needs to be lowered) to provide a teaching and learning environment adequate for strong instructor presence. The ripple effect of this yields positive student satisfaction and student success online.